Hacking digital : best practices to implement and accelerate your business transformation - Wade, Michael; Bonnet, Didier; Yokoi, Tomoko (New York City : McGraw Hill, 2021)
'Practical, proven strategies for transforming your company from a digital dabbler into a full-fledged digital business Several years ago, digital disruption inspired business leaders to rethink and redesign their business model for the digital age. Next, they shifted toward the organizational and cultural aspects of digital transformation. And there they stalled. In fact, up to 90 percent of companies undergoing some form of digital transformation are failing to meet their original objectives. Written by a team of global digital transformation thought leaders, Hacking Digital walks you through the implementation phase by providing the practical advice and information you need to ensure overall success. Equipping you to successfully navigate your business through the entire transformation process, the authors organize Hacking Digital into five thematic sections: Creating a solid foundation for digital transformation Dealing with organizational dynamics and culture Meeting the external challenges you'll inevitably face Generating revenue though digital products and services and business model renewal Building the skills and capabilities required to be an effective leader in a digital environment Sustaining transformation momentum How do you set up digital governance? How do you create successful digital offerings? How do you manage the relationship between digital transformation and IT? Hacking Digital answers these and all the other questions you need to transform your company and seize the competitive edge for years to come'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Business enterprises -- Technological innovations; Information technology -- Management; Organizational change; Organizational effectiveness